Wolves resuming their rightful place in our ecosystem - Rolston, Holmes, 1932-2025, author; Fort Collins Coloradoan, publisher (Colorado State University. Libraries, 1996)
Commentary on seeing the recently re-introduced Yellowstone wolves in the wild. First we heard the howl, spine-tingling, raising goose pimples. Seeing a wolf pack on a kill recalls the age-old love-hate relationship of humans with a majestic animal. Misled by Little Red Riding Hood, we have long misunderstood the wolf. Restoring wolves to Yellowstone is making moral progress.
Keywords: reintroduction; wolves; restoration; Yellowstone National Park